Influences of human activities on Malay civet’s (Viverra tangalunga) occupancy in Sarawak. - Thaqifah Syaza, Jailan; Yi, Melynda Cheok Ka; Kaicheen, Sally Soo; Bouard, Floriane; Jayasilan, Mohd-Azlan (Malaysian Society of Applied Biology, 2018)
Malay Civet, Viverra tangalunga is one of the most commonly recorded carnivores by camera trapping surveys. This species occupies a diverse range of habitat types, therefore, the IUCN Red List classifies this species as Least Concern. Primarily a ground-dwelling species that has a wide distribution in Borneo, the Malay Civet enables a progressed perspective in understanding the effects of human activities towards a highly adaptable species. In this study, six protected areas that were categorized as low, medium and high volume of human activities were compared in relation to the intensity of human activities that corresponds to Malay Civet’s occupancy. Camera traps were placed in six selected protected areas, however the results showed extreme fluctuations between both protected areas under the high classifications of human activities as Gunung Gading National Park (GGNP) has high detection rate of Malay Civet whereas none were detected in Sarawak National Park (SNP). This suggests that high human activities may have influenced the Malay Civet’s activities in a protected area, other factors such as habitat preferences and geographical distribution may have higher influence on Malay Civet’s occupancy and dispersal in Sarawak